1996
DOI: 10.1183/09031936.96.09040758
|View full text |Cite
|
Sign up to set email alerts
|

Lazaroid U-74389F attenuates phorbol ester-induced lung injury in rabbits

Abstract: We examined the effect of the antioxidant lazaroid U-74389F on acute lung injury induced in rabbits by phorbol myristate acetate (PMA).Thirty minutes after receiving either U-74389F (15 mg·kg -1 i.v.) or U-74389F vehicle, rabbits (n=60) were given PMA (60 µg·kg -1 i.v.). PMA vehicle injected rabbits (n=20) served as controls. Over a 5 h period after PMA or PMA vehicle injection, we measured arterial pH, arterial oxygen tension (Pa,O 2 ), arterial carbon dioxide tension (Pa,CO 2 ), and the plasma concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 27 publications
2
9
1
Order By: Relevance
“…Tonoue et al (46) demonstrated that the PaO 2 and PaCO 2 from the lazaroid-treated group were significantly better than control in lung preservation. Miniati et al (49) also documented the same results in rabbit lungs injured by phorbol myristate acetate.…”
Section: Discussionsupporting
confidence: 59%
“…Tonoue et al (46) demonstrated that the PaO 2 and PaCO 2 from the lazaroid-treated group were significantly better than control in lung preservation. Miniati et al (49) also documented the same results in rabbit lungs injured by phorbol myristate acetate.…”
Section: Discussionsupporting
confidence: 59%
“…The protective effects of lazaroids have been reported in many animal models of lung injury [63-64], including the effects of cigarette smoke [65]. Their protective effect is mainly by inhibition of lipid peroxidation.…”
Section: Lipid Peroxidation and Protein Carbonylation Inhibitors/blocmentioning
confidence: 99%
“…Lazaroids (21-aminsteroids, U75412E or trilizad mesylate) are a group of nonglucocorticoid analogues of methyl-prednisolone which are able to penetrate hydrophobic regions of the cell membrane, specifically to prevent peroxidation of membrane lipids [180181]. The protective efficacy of lazaroids has been reported in many animal models of lung injury, such as injury by endotoxin [181], ischemic/reperfusion [182] and tobacco smoke [183].…”
Section: Lipid Peroxidation and Protein Carbonylation Inhibitors/bmentioning
confidence: 99%
“…The protective efficacy of lazaroids has been reported in many animal models of lung injury, such as injury by endotoxin [181], ischemic/reperfusion [182] and tobacco smoke [183]. The findings from the above studies have revealed that lazaroids may exert their protective effect by various mechanisms, inhibition of lipid peroxidation being the main.…”
Section: Lipid Peroxidation and Protein Carbonylation Inhibitors/bmentioning
confidence: 99%